Tropical cyclone activity in the Solomon Islands region: Climatology, variability, and trends. (24th July 2022) - Haruhiru, Alick; Chand, Savin S.; Turville, Christopher; Ramsay, Hamish
Abstract: This study examines the climatology, variability, and trends of tropical cyclones (TCs) affecting the Solomon Islands (SI) territory, in the wider southwest Pacific (SWP), using the South Pacific Enhanced Archive for Tropical Cyclones (SPEArTC) database. During the period 1969/1970–2018/2019, 168 TCs were recorded in the SI territory. A cluster analysis is used to objectively partition these tracks into three clusters of similar TC trajectories to obtain better insights into the effects of natural climate variability, particularly due to the El Niño–Southern Oscillation (ENSO) phenomenon, which otherwise is not very apparent for TCs when considered collectively in the SI region. We find that TCs in clusters 1 and 3 show enhanced activity during El Niño phase, whereas TCs in cluster 2 are enhanced during La Niña and neutral phases. In addition to being modulated by ENSO, TCs in clusters 2 and 3 show statistically significant modulation at an intraseasonal timescale due to the Madden–Julian Oscillation (MJO) phenomenon. There are also some indications through sophisticated Bayesian modelling that TCs in clusters 2 and 3 are slightly influenced by the Interdecadal Pacific Oscillation (IPO). These results can have substantial implications for cluster‐specific development of TC prediction schemes for the SI region. Abstract : Key issue of investigation is that the influence of El Niño–Southern Oscillation (ENSO) is not well defined for the 168 tropical cyclones (TCs) affecting the Solomon Islands territory from 1970 to 2019 (see the figure below). The figure shows (a) map of southwest Pacific region, showing Solomon Islands territory (dashed rectangular region), (b) average number of TCs making longitudinal crossing during various ENSO phases at every 5°, and (c) correlation between total number of observed TCs in SI territory with the Extended Reconstructed Sea Surface Temperature, Version 5 (ERSSTv5) during the months November–April from 1969/1970 to 2018/2019. The key findings are as follows: a cluster analysis is used to partition all the TCs into three clusters of similar trajectories to obtain better insights into the effects of ENSO, which is not very apparent for all TCs in the SI region. We find that TCs in clusters 1 and 3 are enhanced during El Niño phase, whereas TCs in cluster 2 are enhanced during La Niña and neutral phases. Sophisticated modelling also indicates modulation of Interdecadal Oscillations in clusters 2 and 3.